LFA-1/ICAM-1 ligation in human T cells promotes Th1 polarization through a GSK3β signaling–dependent notch pathway - Ong, Seow Theng (2018)
In this study, we report that the integrin LFA-1 cross-linking with its ligand ICAM-1 in human PBMCs or CD4+ T cells promotes Th1 polarization by upregulating IFN-γ secretion and T-bet expression. LFA-1 stimulation in PBMCs, CD4+ T cells, or the T cell line HuT78 activates the Notch pathway by nuclear translocation of cleaved Notch1 intracellular domain (NICD) and upregulation of target molecules Hey1 and Hes1. Blocking LFA-1 by a neutralizing Ab or specific inhibition of Notch1 by a γ-secretase inhibitor substantially inhibits LFA-1/ICAM-1–mediated activation of Notch signaling. We further demonstrate that the Notch pathway activation is dependent on LFA-1/ICAM-1–induced inactivation of glycogen synthase kinase 3β (GSK3β), which is mediated via Akt and ERK. Furthermore, in silico analysis in combination with coimmunoprecipitation assays show an interaction between NICD and GSK3β. Thus, there exists a molecular cross-talk between LFA-1 and Notch1 through the Akt/ERK–GSK3β signaling axis that ultimately enhances T cell differentiation toward Th1. Although clinical use of LFA-1 antagonists is limited by toxicity related to immunosuppression, these findings support the concept that Notch inhibitors could be attractive for prevention or treatment of Th1-related immunologic disorders and have implications at the level of local inflammatory responses.